Anti-Inflammatory Pathways Modulated by Microbial Polysaccharides from Euganean Thermal Muds in Zebrafish - Micol Caichiolo; Raffaella Margherita Zampieri; Francesca Terrin; Annachiara Tesoriere; Fabrizio Caldara; Nicoletta La Rocca; Paolo Martini; Luisa Dalla Valle (Antioxidants)
Thermal mud produced by spas of the Euganean Thermal District (Italy) has been used since ancient times for therapeutic purposes. Recently, the anti-inflammatory activity of microbial polysaccharides (M-PS), extracted from traditionally maturated muds, was demonstrated using the zebrafish model organism. However, the downstream signalling pathways regulated by M-PS remain largely unknown. In this study, to investigate the underlying mechanisms of inflammation resolution, we performed a transcriptome analysis on zebrafish larvae inflamed with copper sulphate and treated with M-PS. Our findings revealed that M-PS treatment down-regulated the expression of key genes involved in several inflammatory pathways. Gene Set Enrichment Analysis identified eleven up-regulated pathways (e.g., TNF-α signalling via NFκB, IL6–JAK–STAT signalling, p53 pathway, apoptosis, and interferon response) with components reduced in number and expression level in M-PS-treated larvae compared to the inflamed ones. Additionally, seven down-regulated pathways were identified (e.g., transcription factors E2F, MYC, and the G2M checkpoint). DEG-pseudotime analysis further confirmed the association of these genes with the pathways identified by GSEA. These results provide valuable insights into the anti-inflammatory properties of M-PS and the therapeutic potential of Euganean thermal muds for inflammatory diseases.